Governance and institutions of transportation investments in U.S. mega‐regions - Vega, Henry L.; Penne, Leo (Transport, 2008)
From a planning perspective, a mega‐region can be defined as an extended network of metropolitan centers and their surrounding areas, crossing county and state lines, linked by integrated labor markets, land use systems and transportation and communication infrastructure. From a governance perspective, delimiting the jurisdictional borders of a mega‐region is rather challenging due to the overlap of hierarchy of governance systems. It has been suggested that the effective management of existing transportation infrastructure and the planning and financing of new investments in these areas will need to operate under a regional framework of governance. What such regional framework might look like is still subject to debate. Despite years in the planning, currently no mega‐regional transportation initiative has been implemented in the U.S. This article uses descriptive and interpretative analysis to further the debate in two areas. It first reviews definitional issues in the existing literature as they apply to mega‐regions and transportation. Second, it undertakes a comprehensive survey of regional initiatives, such as the Corridors of the Future Program, to highlight the complexity of multi‐state transportation projects. Lessons from this survey can be useful when developing future transport policy, as policymakers increase their efforts to adopt regional governance initiatives to finance transportation investments worldwide.First published online: 27 Oct 2010